The Nature of the Savings Function in Developing Countries: A Survey of the Theoretical and Empirical Literature - Mikesell, Raymond F.; Zinser, James E. (Journal of Economic Literature, 2015)
THE savings rate (marginal or average) is regarded as a key performance indicator by development economists, and foreign aid practitioners admonish their clients to increase their savings ratio as a primary condition for achieving a satisfactory rate of economic growth. However, not only have questions been raised regarding the significance of the savings effort as an independent determinant of economic progress, but the formulation of policies designed to increase the savings propensity has suffered from a dearth of knowledge regarding the nature of the savings function in developing countries. A number of alternative savings hypotheses (derived mainly from the literature relating to developed economies) have been advanced, but the paucity of reliable data has made it difficult to test these hypotheses and obtain results which warrant a reasonable degree of confidence. The purpose of this article is: a) to review the theoretical and empirical literature on the savings function in developing countries; b) to assess critically the findings with respect to the major hypotheses; and c) to summarize the state of our knowledge on this important topic. We shall begin with a brief review of the nature of the data on savings in developing countries with which economic analysts must work.